Leveraging Implicit User Feedback in Enterprise Search Retrieval Systems - Nitish Ratan Appanasamy (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Enterprise search systems are fundamentally transforming organizational knowledge management through sophisticated integration of implicit user feedback mechanisms. These advanced systems harness complex user behavior patterns, including detailed click-through rates, engagement time measurements, and comprehensive navigation path analyses. The implementation of refined filtering techniques and position bias compensation methods enables significantly more accurate content discovery while effectively reducing redundant information access. Modern query expansion strategies and real-time click mining further optimize search effectiveness by incorporating deep semantic relationships and nuanced user interaction patterns. Through continuous refinement of implicit feedback processing and intelligent result ranking, enterprise search systems are revolutionizing how organizations access, utilize, and manage their information resources.